A Characterization of Societies with Consistent Majority Decision - Slutsky, Steven (Review of Economic Studies, 1977)
Journal Article A Characterization of Societies with Consistent Majority Decision Get access Steven Slutsky Steven Slutsky Cornell University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 2, June 1977, Pages 211–225, https://doi.org/10.2307/2297062 Published: 01 June 1977